The impact of financial convergence in the economic growth rates of the expansion countries in the euro area - A. H. Al-Juboori, Hayder; A. M. al Shalal, Muhannad; I. A. al Ju bouri, Ghassan (International Journal of Engineering and Technology, 2018)
The Maastricht Agreement included a set of financial and monetary standards that the expan-sion countries committed to implement to ensure economic convergence with the most ad-vanced countries in the European Union. The most important of these criteria is to maintain a moderate debt and deficit ratio to the GDP and to keep interest rates and inflation within a certain ceiling. The implementation of these standards even before joining the Federation in 2003 and it continues to date with the existence of relative differences between countries in the extent of their commitment to the proportions determined and according to the economic situation of both of them in particular and the global economy in general, and the current study was to measure the impact of the development The criteria for monetary and financial convergence referred to above are based on the economic convergence expressed in economic growth (per capita income growth) in seven of the expansion countries. A 13-year study period was adopted with the use of the cross-sectional approach to data processing. The research concluded that the application of convergence criteria In the seven expansion coun-tries contributed to the positive impact on economic growth.Â Â Â